IMPLEMENTASI RPP INTEGRATIF MEMBENTUK KARAKTER KEBANGSAAN UNTUK MEWUJUDKAN BUDAYA LITERASI SISWA - R. NOVIYATI HASYIANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The School Literacy Movement launched by the Ministry of Education and Culture in the school environment is not easy to implement in SMP Negeri 1 Sampang. Students often say it is difficult to complete assignments from the teacher. This is evident when writing activity reports students often say I can't, how do I start and where do I start. The inability of students in literacy is caused by very low interest in reading because students spend more time with gadgets. Here the researcher as a social studies teacher carries out a strategy of integrated learning activities with Civics, PAI, Indonesian language, and cultural arts subjects, Best practice using the Discovery Learning method through the media screening of the G30S/PKI event documentary. Integrative RPP material with the theme Political Development in Indonesia for class IX odd semesters is able to create a literacy culture at SMP Negeri 1 Sampang. This is evidenced by the increase in the number of students who are able to complete assignments by 88%, from 12% to 100%. ABSTRAKGerakan Literasi Sekolah yang dicanangkan oleh Kemendikbud di lingkungan sekolah tidaklah mudah untuk dilaksanakan di sekolah SMP Negeri 1 Sampang. Siswa sering kali mengatakan sulit untuk menyelesaikan tugas dari guru. Hal ini terbukti ketika menuliskan laporan kegiatan seringkali siswa mengatakan saya tidak bisa, bagaimana saya memulainya dan dari mana saya memulainya. Ketidak mampuan siswa dalam berliterasi disebabkan oleh minat baca yang sangat rendah karena siswa lebih banyak menghabiskan waktunya dengan gawai. Disini peneliti selaku guru IPS melakukan strategi kegiatan pembelajaran berintegrasi dengan mata pelajaran PPKn, PAI, Bahasa Indonesia, dan seni Budaya, Best practice menggunakan metode Discovery Learning melalui media pemutaran film documenter peristiwa G30S/PKI. Materi RPP Integratif dengan tema Perkembangan Politik di Indonesia kelas IX semester ganjil mampu mewujudkan budaya literasi di SMP Negeri 1 Sampang. Hal ini dibuktikan dari peningkatan jumlah siswa yang mampu menyelesaikan tugas sebesar 88% yaitu dari 12% menajadi 100%